Predictors of purchase intention mediated by customer satisfaction - Duche-Pérez, Aleixandre Brian; Gutiérrez-Aguilar, Olger, Albino; Hillpa-Zuñiga, Manuel Edmundo; Escobar-Juárez, Antonio Miguel; Romero, Ángela Valeria Mya Pazo; García-Toledo, Lourdes Cecilia; Flores-Vilca, Ivonne Virginia (Edelweiss Applied Science and Technology, 2025)
This study examines the factors influencing purchase intention, with a particular focus on the mediating role of customer satisfaction in consumer decision-making. Understanding these determinants is essential for businesses aiming to enhance consumer engagement and maintain a competitive market position. The research adopts a quantitative approach, utilizing data collected through structured surveys. Structural equation modeling (SEM) is employed to evaluate the relationships among key predictors, including perceived price, comfort, mood, and establishment innovation, as well as their impact on purchase intention. The findings reveal that customer satisfaction significantly mediates the relationship between perceived price, comfort, and purchase intention. Furthermore, mood and establishment innovation serve as moderating factors, reinforcing consumer engagement and fostering positive purchasing behavior. The study underscores the importance of these elements in shaping consumer preferences. To enhance purchase intention, businesses should prioritize customer satisfaction by refining pricing strategies, improving in-store comfort, and cultivating positive emotional experiences. The results offer valuable insights for marketers and business owners, emphasizing that strategic investments in customer experience, pricing, and innovation can effectively drive purchase intention and foster long-term customer loyalty.